Peran Sosial Majlis Taklim (Perintisan Majlis Taklim Az-Zahra, Gondoriyo, Ngaliyan Sebagai Lembaga Amil Zakat) - Nasihun Amin (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
This paper attempts to unravel efforts made a majlis taklim to transform into an amil zakat institutions. The role of zakat institutions will be more pronounced benefits than just being a majlis taklim. It is to embody the image of Indonesian Islam as a representation of Islam, especially in relation to Social-economic welfare, should be formed either amil zakat institutions. Which of course is not merely the responsibility of the large organizations, but also social institutions that are rooted down to the lowest level so that the impact is even really be felt by the community. One of them is the Majlis Taklim az-Zahra who had attempted to pioneer its existence not merely as a study group that only focuses on spirituality problems alone, but also perform a variety of social activities. Especially after held assistance through various activities both workshops, studies, comparative studies and so forth. Proven has started there is a small movement that is gathering a bit of money every week when there recitation